EDUCATION ON THE IMPACT OF BULLYING ON THE MENTAL HEALTH OF ADOLESCENTS IN PESANTREN VILLAGE, TEMBELANG DISTRICT, JOMBANG REGENCY - Fatmawati, Zeny; Barir, Baroroh; Sarmin, Sukati; Putra, Kusuma Wijaya Ridi (Journal of Indonesian Public Health Service, 2024)
Background: Bullying behavior causes serious negative impacts on the victim in the short and long term. Physical violence received by the victim caused by the perpetrator causes depression pressure and feelings of insecurity, resulting in victims not daring to go to school and socialize in the community to meet other people. The impact on the victim in the long term is that it causes the victim to experience emotional problems, low self-esteem, and difficulty socializing, which can cause feelings of suicide, of course, this reflects disturbed mental health. Objective: This service activity aims to increase understanding of the impact of bullying on adolescent mental health so that this negative behavior does not occur in adolescents. Method: This community service activity uses lecture and discussion methods which are carried out at Mrs. Mukhoyaroh's house in Pesantren village after the religious study event., on August 10, 2024. This activity of course begins with the preparation of materials, and location permission from the host and the head of the youth study group. Results: After providing education about the meaning of bullying, types, who are at risk of being bullied, the impact on mental health, and efforts to prevent bullying behavior Most teenage girls understand the impact of bullying on mental health, which can affect the psychological condition of teenagers in socializing with peers, teachers, and the community. the youth discussion session asked questions about what happens when bullying occurs, if it happens at school, immediately ask for help from the teacher and try to resist so that it doesn't happen again. Conclusion: This activity is very useful for teenagers in increasing knowledge that negative behavior such as bullying can have a bad impact on teenagers' mental health. Parents must provide emotional support to students or teenagers who are victims of bullying. Guidance and counseling program services are provided by the school. Must more intensively guide students or teenagers in preventing bullying.